2021
DOI: 10.1177/13591053211064984
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the laboratory into the home: A protocol for remote biobehavioral data collection in pregnant women with emotion dysregulation and their infants

Abstract: Pregnant women struggling with emotion dysregulation may be more likely to engage in a wide range of health risk behaviors. This protocol describes a study on intergenerational transmission of emotion dysregulation from the third trimester of pregnancy to 18 months postpartum. Biobehavioral markers of emotion dysregulation are typically measured in laboratory settings which was prohibited by many universities during the COVID-19 pandemic. We describe how markers of emotion dysregulation (e.g. maternal, fetal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Compared to infants of less dysregulated mothers, infants of highly dysregulated mothers were slower in returning to their RSA homeostatic points. In studies applying traditional regression approaches to model infant RSA, infants of less sensitive or emotionally dysregulated mothers did not exhibit RSA recovery following the stress of the Still‐Face episode (Conradt & Ablow, 2010; Gao et al, 2022). However, without a dynamic systems‐informed analysis, it is difficult to discern whether the lack of RSA recovery reflects a delayed stress response (i.e., RSA level does not change until moments later) or a more rigid moment‐to‐moment physiological responding (i.e., RSA level is changing but in slow speed).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to infants of less dysregulated mothers, infants of highly dysregulated mothers were slower in returning to their RSA homeostatic points. In studies applying traditional regression approaches to model infant RSA, infants of less sensitive or emotionally dysregulated mothers did not exhibit RSA recovery following the stress of the Still‐Face episode (Conradt & Ablow, 2010; Gao et al, 2022). However, without a dynamic systems‐informed analysis, it is difficult to discern whether the lack of RSA recovery reflects a delayed stress response (i.e., RSA level does not change until moments later) or a more rigid moment‐to‐moment physiological responding (i.e., RSA level is changing but in slow speed).…”
Section: Discussionmentioning
confidence: 99%
“…All study procedures were approved by University of Utah's Institutional Review Boards. More details about recruitment, study design, eligibility criteria, and assessment procedures can be found in Gao et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in the field of perinatal mental health includes: contextualized measures of parental perinatal exposures including socioeconomic disadvantage measures, racial/ethnic discrimination and environmental factors in single cohort [109,151,152] and multicohort studies [8, 135,[153][154][155][156][157][158][159][160][161]162 && ]; improvement in measures of offspring neurobehavioral development, including neuropsychological and neuroimaging studies which take relevant and necessary confounders [163] into account [164][165][166][167] and scan the offspring at different ages [31,168 && , [169][170][171][172][173]; studies of the influence of genetic architecture as well environmental toxins and early-life adversity (including poverty) on neurobehavioral development [8, 109,135,158,159,[174][175][176].…”
Section: Progress and Challenges In Pre/perinatal Mental Health Researchmentioning
confidence: 99%
“…Potential solutions to these barriers include remote assessments that can be conducted at a time convenient to the family. For example, in response to the pandemic, our lab (Gao et al, 2022) and others (Tabachnick et al, 2022) have found ways to support families by collecting physiological data in the home.…”
Section: Gaps In Emotion Dysregulation Researchmentioning
confidence: 99%